Checkpoint-dependent and independent roles of the Werner syndrome protein in preserving genome integrity in response to mild replication stress - Basile, Giorgia (Nucleic Acids Res, 2014)
Werner syndrome (WS) is a human chromosomal instability disorder associated with cancer predisposition and caused by mutations in the WRN gene. WRN helicase activity is crucial in limiting breakage at common fragile sites (CFS), which are the preferential targets of genome instability in precancerous lesions. However, the precise function of WRN in response to mild replication stress, like that commonly used to induce breaks at CFS, is still missing. Here, we establish that WRN plays a role in mediating CHK1 activation under moderate replication stress. We provide evidence that phosphorylation of CHK1 relies on the ATR-mediated phosphorylation of WRN, but not on WRN helicase activity. Analysis of replication fork dynamics shows that loss of WRN checkpoint mediator function as well as of WRN helicase activity hamper replication fork progression, and lead to new origin activation to allow recovery from replication slowing upon replication stress. Furthermore, bypass of WRN checkpoint mediator function through overexpression of a phospho-mimic form of CHK1 restores fork progression and chromosome stability to the wild-type levels. Together, these findings are the first demonstration that WRN regulates the ATR-checkpoint activation upon mild replication stress, preventing chromosome fragility.